The Effect of Board Characteristics and Company Size on Tax Transparency - Azadeh Maddahi (پژوهش‌های تجربی حسابداری)
The purpose of this research is to investigate the effect of board characteristics and company size on tax transparency. Tax transparency means properly measuring, presenting and disclosing the amount of tax in the financial statements. Tax transparency, in addition to the proper fulfillment of the company's social responsibility (from the perspective of identifying and paying tax obligations according to the tax law), will help the investors and tax system policymakers to make appropriate decisions. In this research, tax transparency was measured with five criteria (disclosure of tax status, absence of material distortions in tax reserve, absence of significant ambiguity regarding taxes, absence of material annual adjustments for tax, and speed in determining the final tax filing). Also, the effect of the board characteristics on two levels, including the level of the components of board characteristics (size, independence and financial knowledge of the board, the non-executive chairman and the non-duality of the role of the CEO) and the level of the combined criteria of characteristics, were tested with the correlation research method. Results showed that the combined measure of the characteristics has a direct impact on tax transparency. At the component level, the size and financial knowledge of the board have a direct impact, but independence of the board, non-duality of the CEO's role, and the non-executive chairman do not have a significant impact on tax transparency; Company size also has no significant effect on tax transparency.